Inocuidad de Biomasa de Larva de Mosca para uso Pecuario Sostenible - Guzmán Abalco, Cinthya Elizabeth (2019)
This research project was carried out in order to know if the larvae of the fly produce any damage in the birds that consume them. Fly larvae are a resource that can be used for animal feed, because the source of protein used for the preparation of animal feed comes from fish, causing a large environmental impact and bioaccumulation of toxins in fish and fish. Humans. The national aquaculture sector also depends on the supply of fishmeal. It is estimated that 40% of the national production of this product is destined to supply the balanced industry, leading to overexploitation and decreasing the amount of fish in the sea, an option to reduce this overexploitation is the larva of fly that will be used as food of animals. These fly larvae will give rise to several by-products with different applications, such as an ecological humus fertilizer of excellent quality or large amounts of biomass applicable in animal feed, for example, in poultry use. As an alternative for the reduction of fishmeal consumption has been made, obtaining fly larva biomass from decomposing animal tissues, which were analyzed to determine the presence of pathogenic microorganisms and microbial toxins in the production of larva fly The results of the analyzes obtained in the laboratory were compared with the NTE INEN 1829: 2014 and the analyzed parameters are within the permissible range, the fly larva being a good quality food because it indicates the absence of pathogens in the larvae of fly